2006
DOI: 10.1590/s0103-84782006000200040
|View full text |Cite
|
Sign up to set email alerts
|

Digestibilidade aparente da dieta e balanço do nitrogênio em suínos de diferentes grupos genéticos com ou sem restrição alimentar

Abstract: RESUMO Um experimento foi realizado com o objetivo de estudar a digestibilidade aparente da dieta e o balanço do nitrogênio em suínos de diferentes grupos genéticos com ou

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 18 publications
0
1
1
Order By: Relevance
“…Average BW, ADG and DFI values obtained in this trial were slightly lower than those obtained for this line in previous trials on the same experimental farm [19,20,25,30,31]. In general, the results of this study seem to indicate that selection for the growth rate during the growing period has not been effective in this line.…”
Section: Discussioncontrasting
confidence: 83%
“…Average BW, ADG and DFI values obtained in this trial were slightly lower than those obtained for this line in previous trials on the same experimental farm [19,20,25,30,31]. In general, the results of this study seem to indicate that selection for the growth rate during the growing period has not been effective in this line.…”
Section: Discussioncontrasting
confidence: 83%
“…Silva and Silva (2015) reported that genetics, age, diet composition, and room temperature have a direct effect on animal metabolism. Sartor et al (2006) reported that studies with pig commercial crosses, besides presenting variable results, do not consider differences among commercial crosses. In addition, the aforementioned authors did not observe any effect of commercial crosses on apparent digestibility of DM and CP in commercial crosses of grower pigs (Agroceres, Dalland, and Embrapa), which agrees with our findings.…”
Section: Resultsmentioning
confidence: 99%